A reflection upon methods to explore timing in patients with schizophrenia. Issue 1 (26th March 2019) - Martin, Brice; Franck, Nicolas; Giersch, Anne
Abstract: Phenomenologists have provided a detailed description of the disorders of the subjective experience associated with minimal‐self disorders in patients with schizophrenia. Those patients report a range of distortions of their conscious experiences, including a sense of inner void, confusion between self and others, and, sometimes, a disruption of the sense of time. These reports have been interpreted as distortion of the first‐person perspective and a lack of immersion in the world, associated with a breakdown of the temporal structure of consciousness, and especially a disruption of the sense of time continuity. Further, it has been proposed that these disruptions are based on a difficulty to retain past information and to predict future information, that is, the mechanisms that help to relate events with one another and to reach a sense of time continuity. Experimental psychology results seem to converge to similar conclusions, inasmuch as some results in patients with schizophrenia suggest a deficient ability to predict sequences of events at the millisecond level. Several studies have underlined this convergence. Here we reflect on the limits of both the phenomenological and experimental psychology approaches, and of the convergence of their hypotheses. We think that this reflection is necessary to avoid premature conclusions on the mechanisms underlying the impairments in patients, but also to enrich our understanding of schizophrenia.